2015
DOI: 10.2134/jeq2015.01.0036
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Enhanced‐Efficiency Nitrogen Fertilizers on Greenhouse Gas Emissions in a Coastal Plain Soil under Cotton

Abstract: Enhanced-efficiency N fertilizers (EENFs) have the potential to increase crop yield while decreasing soil N loss. However, the effect of EENFs on greenhouse gas (GHG) emissions from different agricultural systems is not well understood. Thus, studies from a variety of locations and cropping systems are needed to evaluate their impact. An experiment was initiated on a Coastal Plain soil under cotton ( L.) production for comparing EENFs to traditional sources. Nitrogen sources included urea, ammonia sulfate (AS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…The latter value is at the upper level of N 2 O emissions from the limited amount of data available for irrigated cotton reported from other countries (Mahmood et al 2008;Scheer et al 2008;Liu et al 2010;Watts et al 2015) and of a similar magnitude to that reported by Grace et al (2004) at the same site. Scheer et al (2008) reported a comparable response to N in irrigated cotton in Uzbekistan (6.5 kg N 2 O-N ha -1 ) after application of 250 kg N ha -1 .…”
Section: Resultssupporting
confidence: 87%
“…The latter value is at the upper level of N 2 O emissions from the limited amount of data available for irrigated cotton reported from other countries (Mahmood et al 2008;Scheer et al 2008;Liu et al 2010;Watts et al 2015) and of a similar magnitude to that reported by Grace et al (2004) at the same site. Scheer et al (2008) reported a comparable response to N in irrigated cotton in Uzbekistan (6.5 kg N 2 O-N ha -1 ) after application of 250 kg N ha -1 .…”
Section: Resultssupporting
confidence: 87%
“…The inconsistent effects of Agrotain Plus on N 2 O emissions observed here were in contrast to some results with Agrotain Plus in corn, which have shown significant mitigation of N 2 O emissions (Halvorson et al, 2014; Thapa et al, 2016). However, Watts et al (2015) also reported no effect on N 2 O emissions from DCD and NBPT addition to solid urea applied in rainfed cotton in Alabama in a 3‐yr study. The DCD in Agrotain Plus probably breaks down quickly in high temperature environments, making its use as an N 2 O emission inhibitor inconsistent (Bronson et al, 1989).…”
Section: Discussionmentioning
confidence: 95%
“…As stated above, correlations between N 2 O emission and soil water or temperature were inconsistent. Watts et al (2015) reported positive correlations between N 2 O emissions in rainfed cotton and soil temperature and soil moisture in 2 of 3 yr. The absence of N 2 O emissions in the second half of the season in FI and OSI from 2012 to 2015 was likely due to the fact that N fertilization events were finished and that large plant biomass N uptake removed most of the available soil NO 3 , and not due to a lack of soil moisture.…”
Section: Discussionmentioning
confidence: 96%
“…In various agroecosystems, slow-release fertilizers have reduced N 2 O emissions compared to fastrelease fertilizers [20][21][22][23][24]. There is some evidence that coatings on URE can reduce the hydrolysis rate, which reduces gaseous losses of nitrogen [25][26][27].…”
Section: Introductionmentioning
confidence: 99%